Characteristics and neuropsychological impact of traumatic brain injury in female prisoners. (5th January 2021) - O'Sullivan, Michelle; Fitzsimons, Steven; Ramos, Sara da Silva; Oddy, Michael; Sterr, Annette
ABSTRACT: Objective : To investigate the characteristics of head injury (HI) and its association with offending behaviour, psychological and neurobehavioral functioning, and cognitive performance in female prisoners. Methods : Using a cross-sectional design, female prisoners in the UK reporting a HI with a loss of consciousness (LOC) over ten minutes (n = 10) were compared with a group without a HI with LOC over ten minutes (n = 41) across a range of measures; including scores on standardized clinical questionnaires and performance-based cognitive assessments. Semi-structured clinical interviews assessed HI and forensic history, with forensic history triangulated against the prison database. Results : Domestic abuse was the most frequently reported cause of HI. The HI with LOC group had been to prison a greater number of times and had committed a greater number violent offences. No significant difference was found on self-reported psychological and neurobehavioral measures, or between the groups' cognitive functioning on neuropsychological tests. Conclusions : Psychosocial factors such as trauma may contribute to higher rates of violent offending and imprisonment in those with a HI with LOC. Domestic abuse is an important factor in HI amongst female prisoners. Forensic screening and interventions need to be designed, adapted and evaluated with consideration of trauma and HI.